Building on the positives: A psychometric review and critical analysis of the construct of Psychological Capital. Issue 3 (12th February 2013) - Dawkins, Sarah; Martin, Angela; Scott, Jenn; Sanderson, Kristy
Abstract : The construct of Psychological Capital (PsyCap) focuses on the positive psychological capacities of self‐efficacy, hope, optimism and resilience and their relationship with a range of desirable work attitudes, behaviours and organizational outcomes. There is now almost a decade of accumulated PsyCap research. However, a critical and synthesized analysis of the construct in terms of its theoretical conceptualization and psychometric properties is yet to appear in the literature. Consequently, this article aims to provide a comprehensive review and analysis of the PsyCap literature, focusing in particular on issues relevant to the psychometric profile of PsyCap as it is currently assessed. Six directives for advancing PsyCap research are proposed as part of an integrated research agenda aimed towards strengthening the conceptualization and measurement of PsyCap. Practitioner points: This article provides a critical and synthesized psychometric‐focused review of the PsyCap construct and its application in the workplace. Several shortcomings of the construct and its primary measure are highlighted. Directives are proposed to further enhance the conceptualization and measurement of the construct and thus enhance its utility in the workplace.